IMPLEMENTASI KEBIJAKAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA KELALAIAN YANG MENYEBABKAN KEMATIAN(Studi Surat Edaran Jaksa Agung Muda Tindak Pidana Umum Nomor 01/E/EJP/02/2022 Tentang Pelaksanaan Penghentian Penuntutan Berdasarkan Keadilan Restoratif) - Azam Akhmad Akhsya, (2024)
Requests for termination of prosecution of perpetrators of criminal negligence that cause death can be rejected or granted even if they use the same technical guide, namely Circular Letter of the Solicitor General for General Crimes Number 01/E/EJP/02/2022. Based on this background, the research focuses on understanding the parameters of restorative justice policies against perpetrators of negligence that cause death and the ideal implementation of restorative justice for perpetrators of negligence. This research is normative juridical research with a statutory approach, case approach, and conceptual approach. The request for Restorative Justice was granted because the parameter of negligent acts was not purely in the perpetrator's self but was also carried out by the victim himself. In contrast, the request was rejected because culpa only came from the perpetrator's actions. The ideal implementation of a restorative justice policy must lead to efforts to restore it to its original state, ensure there is no negative stigma from the community, and it is oriented towards technical efficiency and legal certainty for the parties. The research results suggest that the termination of cases based on restorative justice requires certainty of technical regulations, for example, through the Attorney General's Regulations. The ideal implementation of restorative justice policies must pay attention to a unified written policy/lex scripta that is publicly accessible, testable, integrative between justice mechanisms, functional differentiation of criminal justice, and the harmonization of subjects and objects in prosecutions.